Al-Quran Digital Vs Al-Quran Cetak: Menjelajahi Perspektif Mahasiswa Terhadap Pemanfaatannya Dalam Dimensi Globalisasi - Aam Abdussalam; Mohammad Rindu Fajar Islamy; Muhamad Parhan (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2021)
The presence of the development of technology 4.0 as well as the transformation of changes in the flow of globalization really have a significant influence on the joints of the life of modern society. Changes in culture, culture, thought patterns, activity patterns, politics, economics, and even the world of education today are more likely to reduce individual spiritual values among students. There is a need for serious efforts by practitioners of the world of education in restoring the enthusiasm of students to explore the study of the Al-Quran so as to encourage them to increase individual religiosity and piety. The existence of the Digital Al-Quran also encourages their interest in exploring the depths of the meaning of the content of the Al-Quran, this is certainly a positive effort that must be preserved. This study aims to explore student responses in optimizing the use of the Digital Al-Quran with the Printed Al-Quran. The research method was designed using a mix method approach, combining a combination of questionnaires with random sampling techniques as well as an in-depth interview process with religious officials of the Indonesian Ulama Council of Lembang Regency and the Bandung City PCNU board in order to validate the existing data findings. The number of respondents in this study were 41 people, most of which were students at one of the Bandung universities. The results of the study prove that there are positive and negative sides of using the Digital Al-Quran among them, besides that this application is able to increase individual piety in the midst of the dimensions of modernity and globalization.